Evaluasi Kebijakan Relokasi Pasar Barito Kota Semarang Tahun 2018 Studi Kasus Relokasi Pasar Barito ke Pasar Barito Baru Penggaron - Adelina Saraswati; Achmad Taufiq (Journal of Politic and Government Studies, 2020)
The Semarang Barito market relocation policy 2018 is the action of SemarangCity governor to overcome the problem caused by usages of the riverbank of theEast Flood Canal (BKT) by Barito Market traders, which consists of thenarrowing of the river flow, sedimentation, risk of flooding, seedy view, andincreasing number of illegal buildings as shelter as well as a place of business.The relocation is intended to free the riverbank of BKT as well as moving andmanaging Barito market traders to the Barito Baru Penggaron market.The author employed the descriptive qualitative method with the technique ofcollecting data through interviews, literature, and documentation. The author used the theory of policy assessment from William N. Dunn to evaluate the relocation policy of the Semarang City Barito market in 2018 with a case study of the Barito Market relocation to the Barito Baru Penggaron market according to five evaluation indicators to improve the performance and increase the support for the relocation policy.Based on indicators of adequacy, equity, responsiveness, and accuracy, therelocation policy of the Barito market has been implemented and has met thetarget based on objectives and results, even though some traders are lesssupportive and dissatisfied with their relocation. This has an impact on tradersactivities at the Barito Baru Penggaron market.The author recommends for the Semarang City Governor, both the SemarangCity Trade Office and other Regional Organizations (OPD) to make properpreparations based on the previously planned agenda, to plan the budget for allactivities before and after the implementation for building and managing themarket and traders, also to create an evaluation for relocation policy of Semarang Barito market for future policy.Keywords : Policy Evaluation, Relocation, Traders, Barito Market, Barito Baru Penggaron Market